2021
DOI: 10.1021/acschembio.1c00411
|View full text |Cite
|
Sign up to set email alerts
|

OFF-State-Specific Inhibition of the Proprotein Convertase Furin

Abstract: The pro-protein convertase furin is a highly specific serine protease involved in the proteolytic maturation of many proteins in the secretory pathway. It also activates surface proteins of many viruses including the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Furin inhibitors effectively suppress viral replication and thus are promising antiviral therapeutics with broad application potential. Polybasic substrate-like ligands typically trigger conformational changes shifting furin’s active si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 47 publications
(95 reference statements)
0
16
0
Order By: Relevance
“…Compounds 1−5 were synthesized as described previously 16 Furin was expressed, purified, and crystallized as described previously. 5,25,15 On the basis of the fit to the electron density map, the R and S enantiomers of 2 and 5, respectively, were modeled in the structures.…”
Section: ■ Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Compounds 1−5 were synthesized as described previously 16 Furin was expressed, purified, and crystallized as described previously. 5,25,15 On the basis of the fit to the electron density map, the R and S enantiomers of 2 and 5, respectively, were modeled in the structures.…”
Section: ■ Methodsmentioning
confidence: 99%
“… 12 , 13 Structural studies revealed different interaction patterns of these compound classes compared with canonical furin inhibitors. 14 , 15 Thus, noncanonical small-molecule furin inhibitors might be a promising opportunity to identify more drug-like compounds with improved bioavailability.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of note, these compounds are not required to be positively charged to establish electrostatic interaction with the active site of furin, which overcomes the limitation of poor cell permeability [ 44 ]. In another study, guanyl hydrazone inhibitors evidenced an active site-directed binding mode to the furin OFF-state conformation [ 45 ]. The compounds were found to interact with the S1 pocket and with a second binding site at the S4 / S5 pocket of furin.…”
Section: Furin Inhibition and Sars-cov-2 Infectionmentioning
confidence: 99%
“…SARS-CoV-2 bears a polybasic sequence PRRAR at the S1/S2 cleavage site that can be cleaved by furin (Hoffmann et al, 2020a;Peacock et al, 2021). Several peptide-based and small-molecule inhibitors of furin have been developed (Dahms et al, 2021;Osman et al, 2022). A combination of the furin inhibitor MI-1851 (Figure 1Bc) with various TMPRSS2 inhibitors enhances the antiviral potency (Bestle et al, 2020).…”
Section: Host Proteasesmentioning
confidence: 99%